Desarrollo y formación de la variedad de maiz V-533 para el sistema de producción de roza-tumba-quema - Castillo González, R.A.=700 1 Aguilar Castillo, G.; Rodríguez Sánchez, J.; Poot, V.M.
Sumario (Es)
Ilus.; 4 ref.
Keywords: ZEA MAYS; VARIEDADES; SISTEMAS DE CULTIVO; MEXICO